THE EFFECT OF MAKE A MATCH TECHNIQUE ON STUDENTSâ€™ READING COMPREHENSION AT JUNIOR HIGH SCHOOL - Zurnelli, Netti; Anggraini, Desti; Widia (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2022)
The primary objective of this study is to investigate the impact and variations associated with the utilisation of the make a match strategy on the reading comprehension abilities of pupils. The present work employs a quantitative approach and adopts a quasi-experimental methodology. The research was carried out using two distinct groups, specifically the experimental group and the control group. The participants in this study consisted of students from class VIII A and VIII B of SMP Negeri 20 Kabupaten Tebo. The participants in this study consisted of a total of 34 students, with 17 students assigned to the experimental class and another 17 students assigned to the control class. The average findings obtained from both courses were subjected to statistical analysis using a T-test, with a significance level of Î± = 0.05. This phenomenon is observable in both the paired sample T-test and the independent sample T-test. The findings indicate that the mean reading comprehension score of students who received instruction using the make a match technique was 1.175. This result aligns with the hypothesis criteria, which states that a score below 5% would be considered low. A significance level of 0.05 indicates that the alternative hypothesis (Ha) is accepted. Therefore, it can be inferred that the implementation of the make a match strategy has a notable impact on the development of students' learning abilities. In the interim, the outcomes of the independent sample t-test indicated a mean difference of 4.824 and a two-tailed significance level of 0.05 (1.175 â‰¤ 0.05). Based on the aforementioned description, the null hypothesis (Ho) is rejected, whereas the alternative hypothesis (Ha) is accepted. This indicates a notable disparity in the application of the make a match strategy between the experimental group and the control group in relation to the enhancement of students' reading proficiency at SMP Negeri 20 Kabupaten Tebo.